QUIET STUDENTS IN THE DIGITAL EDUCATION ERA: LITERATURE ANALYSIS ON SOCIAL-EMOTIONAL CHALLENGES AND PSYCHOLOGICAL COUNSELING STRATEGIES - Jannatul Ma'wa; Aisyah Maretha Putri; Dimas Aditya Syaukani; Adelia Virnanda Putri Suhadi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
The phenomenon of quiet students has become increasingly evident in today’s era of digital education. The transformation from face-to-face learning to online modes has significantly influenced students’social and emotional conditions, particularly among those who are more vulnerable to social anxiety, low learning motivation, and reduced academic engagement. This study aims to explore the psychological and pedagogical factors contributing to the emergence of quiet students in digital learning contexts, as well as to formulate appropriate psychological mentoring strategies. The research employs a literature analysismethod, focusing on five recent studies related to social anxiety, learning motivation, digital literacy, andstudent engagement in online learning. The findings reveal that quiet students in digital environments often face communication barriers, low self-confidence, and a lack of emotional support from academic settings. Additional challenges arise from limited digital literacy and insufficiently interactive teaching methods. Empathic mentoring strategies grounded in Bandura’s theory of self-efficacy, Lazarus’s coping stress framework, and Goleman’s emotional intelligence model are applied to develop psychological approaches.